2012
DOI: 10.1590/s0102-311x2012000800002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de síndrome metabólica e seus componentes na transição menopáusica: uma revisão sistemática

Abstract: A síndrome metabólica é um transtorno complexo, caracterizado por um agrupamento de fatores de risco cardiovascular. Sugere-se que a fase da transição menopáusica possa ser um determinante importante no aumento da prevalência da síndrome metabólica. O presente estudo teve como objetivo verificar, por meio de uma revisão sistemática, a prevalência de síndrome metabólica e dos seus componentes na transição menopáusica. Três revisores fizeram a busca dos artigos na base de dados do PubMed. A qualidade dos artigos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
15

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 29 publications
1
13
0
15
Order By: Relevance
“…MS is one factor that increases the mortality rate in both men and women (17). A meta-analysis confirmed this information by describing a higher prevalence of MS during the postmenopausal stage than the premenopausal stage, regardless of population (18). There was a statistically significant relationship between postmenopausal stage and increased age with the presence of MS.…”
Section: Discussionmentioning
confidence: 72%
“…MS is one factor that increases the mortality rate in both men and women (17). A meta-analysis confirmed this information by describing a higher prevalence of MS during the postmenopausal stage than the premenopausal stage, regardless of population (18). There was a statistically significant relationship between postmenopausal stage and increased age with the presence of MS.…”
Section: Discussionmentioning
confidence: 72%
“…Several studies have shown a high prevalence of AO in postmenopausal women, ranging from 50 to 85% [31,[46][47][48][49]. A systematic review by Mendes et al [49] found a high prevalence of AO in the menopausal transition, mainly in studies performed in clinics.…”
Section: Prevalence Of Abdominal Obesitymentioning
confidence: 99%
“…A systematic review by Mendes et al [49] found a high prevalence of AO in the menopausal transition, mainly in studies performed in clinics. Among these, the highest prevalence rates were reported in a study based on the Northeast region of Brazil, with 76.6% of premenopausal women and 85.2% of postmenopausal women.…”
Section: Prevalence Of Abdominal Obesitymentioning
confidence: 99%
“…Then the studies were read and evaluated as to quality, objective, methodological approach used, and findings in relation to the guiding question. An analysis of the methodological quality of the quantitative studies was carried out as recommended in the Strobe statement [15], based on the number of items existing in each study analyzed; they were considered to be of good quality when the studies fulfilled more than 50% of the items required [16]. No evaluation was applied to literature reviews and qualitative studies.…”
Section: Methodsmentioning
confidence: 99%